2021
DOI: 10.1016/j.celrep.2020.108631
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial protein ERAL1 suppresses RNA virus infection by facilitating RIG-I-like receptor signaling

Abstract: Highlights d Mitochondrial protein ERAL1 positively regulates RNA virustriggered innate immunity d ERAL1 can translocate from mitochondria to cytoplasm after viral infection d ERAL1 is released through the BAX/BAK pore in a RIG-I-and MDA5-dependent manner d ERAL1 mediates polyubiquitination and activation of RIG-I and MDA5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 75 publications
(91 reference statements)
0
25
0
Order By: Relevance
“…COG6 and SERINC4 have been suggested to be inhibitors of HIV-1 replication ( Liu et al, 2014 ; Qiu et al, 2020 ), while the expression of AZGP1 , which has been reported to be associated with HPV status, was significantly high ( Poropatich et al, 2019 ). ERAL1 suppressed RNA virus infection by facilitating RIG-I-like receptor signaling ( Li et al, 2021 ), while ORMDL3 was reported to be regulated by IRF-3 as a result of RSV infection by direct binding to the promoter of ORMDL3 ( Wang et al, 2017 ). Evidently, STAT2 , as a transcription regulatory factor, could increase the levels of the interferon-stimulated gene (ISG) and IFN transcripts in response to RV, establishing an antiviral state ( Angel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…COG6 and SERINC4 have been suggested to be inhibitors of HIV-1 replication ( Liu et al, 2014 ; Qiu et al, 2020 ), while the expression of AZGP1 , which has been reported to be associated with HPV status, was significantly high ( Poropatich et al, 2019 ). ERAL1 suppressed RNA virus infection by facilitating RIG-I-like receptor signaling ( Li et al, 2021 ), while ORMDL3 was reported to be regulated by IRF-3 as a result of RSV infection by direct binding to the promoter of ORMDL3 ( Wang et al, 2017 ). Evidently, STAT2 , as a transcription regulatory factor, could increase the levels of the interferon-stimulated gene (ISG) and IFN transcripts in response to RV, establishing an antiviral state ( Angel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protrusion of the IMM through OMM pores generated during MOMP allows for release of immunogenic mitochondrial matrix components, such as mtDNA, mtdsRNA, and ERAL1. While mtdsRNA ( 106 ) and ERAL1 ( 107 ) induce MAVS signaling, mtDNA release activates the cGAS/STING pathway ( 74 , 75 ), the NLRP3 ( 93 96 ) and AIM2 (not shown) ( 75 , 97 ) inflammasome pathways, and TLR9 ( 91 ) signaling. Importantly, caspase-3 cleavage of cGAS and IRF3 regulates whether MOMP leads to inflammatory signaling or apoptosis ( 81 83 ).…”
Section: Activation Of Mitochondrial Cell Death Pathways During Viral Infectionsmentioning
confidence: 99%
“…coli Ra s- l ike 1 (ERAL1) during RNA virus infection by BAX/BAK enhances MAVS signaling in vitro and in vivo during RNA virus infection ( Fig. 1C ) ( 107 ). This ERAL1 activity is RIG-I dependent.…”
Section: Mitochondrial Regulation Of Immune Gene Expression Programs During Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection activates pattern recognition receptors on pulmonary epithelial cells, endothelial cells, macrophages, DCs, and other immune cells to produce cytokines [ 96 , 97 ]. Recognition receptors including Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I, melanoma differentiation-associated gene 5 (MDA5), cyclic guanosine phosphate adenosine phosphate synthase (cGAS), stimulator of interferon genes (STING), and nucleotide-binding oligomerization domain-like receptors (NLRs) play a significant role in antiviral defense against coronaviruses ( Figure 3 ) [ 98 , 99 , 100 ].…”
Section: Ace2 Sars-cov-2 and Innate Immune Pathwaysmentioning
confidence: 99%